2023
DOI: 10.1111/irv.13128
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of endemic coronaviruses during the COVID‐19 pandemic in Iran, 2021–2022

Abstract: Background Human coronaviruses (HCoVs) 229E, OC43, HKU1, and NL63 are common viruses that continuously circulate in the human population. Previous studies showed the circulation of HCoVs during the cold months in Iran. We studied the circulation of HCoVs during coronavirus disease 2019 (COVID‐19) pandemic to find the impact of pandemic on the circulation of these viruses. Methods As a cross‐sectional survey conducted during 2021 to 2022, of all throat swabs sent to Iran National Influenza Center from patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Herein, NL63 was the most prevalent of the four eHCoV species, followed by OC43 ( p < 0.05). Surveillance studies conducted in different countries have shown that the distribution of common eHCoV species varies by year and geographical location [ 20 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herein, NL63 was the most prevalent of the four eHCoV species, followed by OC43 ( p < 0.05). Surveillance studies conducted in different countries have shown that the distribution of common eHCoV species varies by year and geographical location [ 20 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several smart cities around the world have implemented proactive surveillance systems to monitor the spread of pandemics and take timely preventive actions. For instance, Singapore's smart city initiatives have demonstrated remarkable success in leveraging technology for pandemic control [90]. Through their "TraceTogether" program, Singapore implemented a contact tracing system that utilizes Bluetooth technology to identify and notify individuals who have been near COVID-19 cases.…”
Section: Early Detection and Surveillancementioning
confidence: 99%
“…This integrated approach allows for efficient contact tracing and early detection of outbreaks, enabling swift responses, targeted interventions, and effective containment measures. These examples highlight how proactive surveillance systems in smart cities can play a crucial role in monitoring and managing the spread of pandemics, ultimately helping to safeguard public health and minimize the impact of infectious diseases [90].…”
Section: Early Detection and Surveillancementioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first identified in December 2019 during an outbreak originating from a market in Wuhan, China [1]. This novel coronavirus is the cause of coronavirus disease 2019 (COVID- 19) and is only the seventh known coronavirus that has been infectious to humans [2,3]. The rapid spread of COVID-19 has resulted in the World Health Organization (WHO) declaring a global pandemic.…”
Section: Introductionmentioning
confidence: 99%